SHORE SEINES FOR RESERVOIRS - PART II. STUDIES ON OPTIMUM MESH SIZE - VARGHESE, M D; GEORGE, V C; KHAN, A A; IYER, H KRISHNA (Fishery Technology, 2017)
Fish landings by shore seines operated in the Hirakud Reservoir were analysedspecies wise and their morphometrical details were recorded. Based on the above investigation proportionality coefficients in respect of important species of fish wereworked out in order to detetmine the optimum mesh size as this was important from the conservation point of view. This communication discusses the significance of mesh regulation for shore seines.